Training on Education Policy Analysis for Education Stakeholders in Brebes - Nurhayati, Riana; Hajaroh, Mami; Purwastuti, Lusila Andiani; Rohman, Arif (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
The Brebes district youth education and sports office is one of the districts responsible for making education policies based on local wisdom and innovative policies. In addition, the qualifications needed by the Brebes Youth and Sports Education office are as an evidence-based policy maker based on research analysis for policy, policy analysis, policy implementation, and evaluation, which can ultimately provide policy recommendations. However, only some education personnel in Brebes district's education, youth and sports offices have competence in policy analysis. Based on the situation analysis, it is urgent to conduct policy analysis training for education stakeholders, especially the Brebes Regency youth and sports education office. The target audience in this training is stakeholders in the Brebes district, consisting of school principals, supervisors, and administration/managers. The implementation method includes lectures, discussions/questions and answers, educational games, training with problem-based learning, and (post-test) evaluation of training implementation. The training results showed that the participants gave an assessment related to the review of this education policy analysis training in the